Incidence and predictors of hospitalization in patients with atrial fibrillation: results from the Chinese atrial fibrillation registry study - Dong, Zhaojie (BMC Cardiovasc Disord, 2021)
BACKGROUND: Patients with atrial fibrillation (AF) underwent a high risk of hospitalization, which has not been paid much attention to in practice. Therefore, we aimed to assess the incidence, causes and predictors of hospitalization in AF patients. METHODS: From August 2011 to December 2017, a total number of 20,172 AF patients from the Chinese Atrial Fibrillation Registry (China-AF) Study were prospectively selected for this study. We described the incidence, causes of hospitalization by age groups and sex. The Fine-Gray competing risk model was employed to identify predictors of first all-cause and first cause-specific hospitalization. RESULTS: After a mean follow-up of 37.3 ± 20.4 months, 7,512 (37.2%) AF patients experienced one or more hospitalizations. The overall incidence of all-cause hospitalization was 24.0 per 100 patient-years. Patients aged < 65 years were predominantly hospitalized for AF (42.1% of the total hospitalizations); while patients aged 65–74 and ≥ 75 years were mainly hospitalized for non-cardiovascular diseases (43.6% and 49.3%, respectively). We found patients complicated with heart failure (HF)[hazard ratio (HR) 1.10, 95% confidence interval (CI) 1.02–1.18], established coronary artery disease (CAD) (HR 1.24, 95%CI 1.17–1.33), ischemic stroke/transient ischemic attack (TIA) (HR 1.22, 95%CI 1.15–1.30), diabetes (HR 1.14, 95%CI 1.08–1.20), chronic obstructive pulmonary disease (COPD) (HR 1.28, 95%CI 1.02–1.62), gastrointestinal disorder (HR 1.37, 95%CI 1.21–1.55), and renal dysfunction (HR 1.24, 95%CI 1.09–1.42) had higher risks of hospitalization. CONCLUSIONS: More than one-third of AF patients included in this study were hospitalized at least once during over 3-year follow-up. The main cause for hospitalization among the elderly patients (≥ 65 years) is non-cardiovascular diseases rather than AF. Multidisciplinary management of comorbidities should be advocated to reduce hospitalization in AF patients older than 65 years old. Clinical Registryhttp://www.chictr.org.cn/showproj.aspx?proj=5831. Unique identifier: ChiCTR-OCH-13003729. The registration date is October 22, 2013. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12872-021-01951-5.